From rock‐boring organisms to tunnel boring machines: A new rock breaking technology by bioinspiration. Issue 4 (17th September 2021) - Zheng, Jing; Wu, Zhixin; Nie, Jiahui; Lei, Lei; Zhou, Zhongrong; Li, Jianbin
Abstract: The purpose of this study is to achieve better understanding of associated mechanisms and to recommend and identify new strategies to develop new rock breaking technology for Tunnel Boring Machines (TBMs). Tunnel Boring Machine tunnelling mainly depends upon the rock breakage caused by cutters moving on a rock surface in a rolling and sliding motion while under the action of thrust force. The rock breaking behaviour is controlled by the mechanical interaction between the cutters and the rock. Due to the high hardness and high abrasiveness of rock, the cutters have to work under very high thrust force and suffer heavy‐load‐impact and abrasive wear, causing serious wear and low rock breaking efficiency. Rock‐boring organisms exist in nature, which achieve drilling and/or tunnelling in rocks through a tribochemical interaction. This phenomenon is called bioerosion and the organisms are natural 'TBMs' to some degree. In this study, the interaction between TBM cutters and rock is presented, and current measures to improve cutter wear and rock breaking efficiency and their limitations are reported. Then, the connotation, mechanism and typical cases of bioerosion are presented. Finally, inspired by bioerosion, a new chemically assisted rock breaking technology is proposed for TBMs.